Instilling Discipline Based on Teacher Exemplary Behavior in Madrasas: A Literature Review - Ali Yakub; Rumbang Sirojudin; Hunainah; Eti Shobariyah (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Objective: The rapid expansion of digital technologies has intensified adolescents’ exposure to online gambling, raising concerns about its social, educational, and psychological consequences. This study aims to examine patterns of online gambling among adolescents, associated behavioral changes, and the implications for education within the local context of Cilegon City, Indonesia. Method: Using a qualitative document-based research design, the study analyzes secondary data drawn from local statistical reports, policy documents, academic studies, and school- and community-based intervention records related to online gambling. Result: The findings indicate that adolescent engagement in online gambling is facilitated by high digital accessibility, peer influence, and the normalization of gambling elements in online gaming environments. Behavioral changes observed include increased impulsivity, emotional instability, social withdrawal, and distorted perceptions of risk and reward. These behavioral shifts are closely linked to educational consequences such as declining academic engagement, reduced learning motivation, and weakened school attachment. Family and school contexts emerge as critical factors, functioning both as sources of risk and as potential protective environments, depending on the quality of supervision, communication, and institutional support. The study highlights significant gaps in preventive efforts, particularly the lack of structured school-based programs and coordinated home–school interventions. Conclusion: The findings underscore the need for integrated, education-centered prevention strategies and context-sensitive policies to address adolescent online gambling as a multidimensional social and educational issue.